2018
DOI: 10.1051/0004-6361/201833476
|View full text |Cite
|
Sign up to set email alerts
|

A Gaia DR2 view of the open cluster population in the Milky Way

Abstract: Context. Open clusters are convenient probes of the structure and history of the Galactic disk. They are also fundamental to stellar evolution studies. The second Gaia data release contains precise astrometry at the sub-milliarcsecond level and homogeneous photometry at the mmag level, that can be used to characterise a large number of clusters over the entire sky. Aims. In this study we aim to establish a list of members and derive mean parameters, in particular distances, for as many clusters as possible, ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

78
904
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 731 publications
(998 citation statements)
references
References 237 publications
78
904
7
Order By: Relevance
“…The distance to these clusters are found to be 957±152, 982±132, and 2554±387 pc for the clusters NGC 381, NGC 2360, Be 68, respectively. The derived distances are in agreement with the distances of 1024, 970, and 2437 for the clusters NGC 381, NGC 2360, and Be 68 obtained by Cantat-Gaudin et al (2018). The present estimated age of the cluster NGC 381 is 447±52 Myr which is in close agreement with the age ∼500 Myr obtained by Bossini et al (2019) and slightly higher than ∼320 Myr reported by Ann et al (2002) but is significantly less than 1.1 Gyr reported by Phelps & Janes (1994).…”
Section: Age and Distance Through Cmdsupporting
confidence: 90%
See 3 more Smart Citations
“…The distance to these clusters are found to be 957±152, 982±132, and 2554±387 pc for the clusters NGC 381, NGC 2360, Be 68, respectively. The derived distances are in agreement with the distances of 1024, 970, and 2437 for the clusters NGC 381, NGC 2360, and Be 68 obtained by Cantat-Gaudin et al (2018). The present estimated age of the cluster NGC 381 is 447±52 Myr which is in close agreement with the age ∼500 Myr obtained by Bossini et al (2019) and slightly higher than ∼320 Myr reported by Ann et al (2002) but is significantly less than 1.1 Gyr reported by Phelps & Janes (1994).…”
Section: Age and Distance Through Cmdsupporting
confidence: 90%
“…The tidal Table 1. The values of parameters listed in the Cantat-Gaudin et al (2018) and WEBDA for the clusters in the present study. The values of RA, DEC, l, b, Dist.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A correction of 0.005 mas to the median values of our original Gaia DR2 parallaxes gives a closer distance with a difference 0.10 kpc (Juc 9) and 0.05 kpc (Be 97). Gaia DR2 parallax Cantat-Gaudin et al (2018) participating in the Gaia Multilateral Agreement. The Gaia mission website is http://www.cosmos.esa.int/gaia.…”
Section: Discussionmentioning
confidence: 99%